An Update on Endocrine Mucin-producing Sweat Gland Carcinoma - Meghana Agni; Meisha L. Raven; Randy C. Bowen; Nora Laver; Patricia Chévez‐Barrios; Tatyana Milman; Charles G. Eberhart; Steven M. Couch; Daniel Bennett; Daniel M. Albert; R. Nick Hogan; Paul O. Phelps; et al. (2020)
Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a rare, low-grade adnexal neoplasm with predilection for the periorbital skin of older women. Histologically and immunophenotypically, EMPSGC is analogous to another neoplasm with neuroendocrine differentiation, solid papillary carcinoma of the breast. Both lesions are spatially associated with neuroendocrine mucinous adenocarcinomas of the skin and breast, respectively. EMPSGC is ostensibly a precursor of neuroendocrine-type mucinous sweat gland adenocarcinoma (MSC), a lesion of uncertain prognosis. Non-neuroendocrine MSC has been deemed locally aggressive with metastatic potential, and previous works speculated that EMPSGC-associated (neuroendocrine-type) MSC had similar recurrence and metastatic potential with implications for patient follow-up. Only 96 cases of EMPSGC have been reported (12 cases in the largest case series). Herein, we present 63 cases diagnosed as "EMPSGC" in comparison with aggregated results from known published EMPSGC cases. We aim to clarify the clinicopathologic features and prognostic significance of the neuroendocrine differentiation of EMPSGC and its associated adenocarcinoma and to determine the nosological relevance of EMPSGC association in the spectrum of MSC histopathogenesis. Results established an overall female predominance (66.7%) and average presenting age of 64 years. EMPSGC lesions were associated with adjacent MSC in 33.3% of cases. The recurrence rate for neuroendocrine-type MSC was ~21%, less than the reported 30% for non-neuroendocrine MSC. There were no cases of metastasis. EMPSGC and neuroendocrine-type MSC are distinct entities with more indolent behavior than previously reported, supporting a favorable prognosis for patients.